Daily field checking list by Walter Rosene, April 3, 1932 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 3, 1932. This checklist was used by Walter Rosene to record birds sighted near Jewell between 7:00 and 5:00. This checklist is virtually the same as another checklist with this date but with different notes. Plustek--flatbed